Diversity and Screening of Cellulolytic Microorganisms from Mangrove Forests, Natural Parks, Paddy Field, and Sugarcane Plantation in Panay Island, Philippines - Isabel Grace T. Gatpatan; Rhudith B. Cabulong; Resurreccion B. Sadaba (International Journal of Microbiology)
Cellulolytic microorganisms secrete cellulase, which plays a crucial role in the conversion of lignocellulosic biomass into value-added products with diverse applications in industries, such as biofuel, healthcare, and agriculture. As the world transitions to a bioenergy future, cellulase demand is likely to expand. However, the high cost and low catalytic activity of cellulase hinder the commercialization of biorefineries. Searching for cellulase-producing microorganisms in different environments through bioprospecting can aid in broadening the range of cellulases that are currently available. Meanwhile, the cellulolytic activity of marine microorganisms remains largely unexplored, making it difficult to compare the cellulolytic activity of terrestrial and marine environments. Thus, this study aimed to investigate the diversity and activity of culturable cellulolytic microorganisms in four terrestrial and three marine sites within Panay Island, Philippines. The results showed that the cellulolytic microbial load was tenfold higher in the terrestrial sites than in the marine sites, possibly due to the dynamic mangrove environment. Out of the 42 isolates with a high cellulolytic index (CI) of ≥3.0, 36 were from terrestrial and 6 from marine habitats. The CMCase, Avicelase, and FPase activities were then tested on the 18 isolates with the highest CI. It was observed that many isolates had a high CI, but few exhibited high enzyme activities. Marine isolates showed higher CMCase and Avicelase activities, with comparable FPase activity to their terrestrial counterparts. Isolates S1ACP6B from a sugarcane field and MS1OMP2A from a mangrove site exhibited the highest cellulase activities at 0.41 and 0.29 U/mg, respectively, and were identified as Enterobacter roggenkampii and Rhodococcus erythropolis, respectively. Among the 18 identified isolates, three are resistant to chloramphenicol and three isolates are potentially new species of Halomonas sp. MS1ACP1B, Albirhodobacter sp. MP2ACP3B, and Saccharomycetaceae sp. B1CZP10A. Overall, this study provides an insight on the composition of cellulolytic microbial load and their activities among various habitats.